Math Problem Statement
without using truth table prove (~pvq)^(p^(P^q))
Solution
To prove the logical equivalence of the expression , we can simplify the expression using logical identities. Here's the step-by-step proof:
Step 1: Simplify the expression
Consider the given expression:
This expression is a conjunction () of two components: and .
Step 2: Distribute over the conjunction
The expression can be expanded by distributing over the conjunction:
[ [(\neg p \vee q) \wedge p] \wedge [(\neg p \vee q) \wedge (\neg p \vee q)] ]
Since simplifies to , the expression becomes:
Step 3: Simplify the conjunction
Now, consider the conjunction . This can be rewritten using the distributive law:
Since is a contradiction (i.e., always false), it simplifies to:
This further simplifies to:
Thus, the original expression simplifies to:
Step 4: Distribute over the conjunction
Distribute over the conjunction:
[ [q \wedge p \wedge \neg p] \vee [q \wedge p \wedge q] ]
Step 5: Simplify each term
-
The term is a contradiction, as and cannot both be true, so this term simplifies to false.
-
The term simplifies to , because is just .
So the entire expression simplifies to:
Conclusion:
Thus, the original expression simplifies to . Therefore, is logically equivalent to .
Would you like further details or have any questions?
Here are some related questions:
- What is the distributive law in logic?
- How does the distributive law apply to conjunctions and disjunctions?
- What is the significance of contradictions like in logic?
- How can logical identities be used to simplify complex expressions?
- What are common pitfalls when simplifying logical expressions?
Tip: When simplifying logical expressions, always look for contradictions like or tautologies like , as they can drastically simplify the expression.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Logic
Logical Equivalence
Conjunction
Distributive Law
Formulas
-
Theorems
-
Suitable Grade Level
Advanced High School / College
Related Recommendation
Proving Logical Equivalence: (p ∧ ¬q) ∨ (p ∧ q) = p Using Distributive, Tautology, and Identity Laws
Understanding Logical Equivalence and Implications in Logic: Simplifying p ∨ (p ∧ (q ∨ (q ∧ p))) ≡ p ⟹ q
Proof of Logical Equivalence: p ∨ (¬p ∧ ¬q) ∨ (p ∧ q) = p ∨ (¬p ∧ ¬q)
Proving Logical Equivalence: ¬(p ∧ ¬¬(p ∨ q)) ≡ ¬p
Proving Logical Equivalence: p → q^ [¬q^r∨ ¬q] ⇔ ¬(q ∨ p)